The Influence of Realistic Mathematics Education and Learning Discipline on Students' Mathematical Critical Thinking - Hartiningsih, Syayida Wahyu; Sasmita, Karta; Novianti, Idha (Global Synthesis in Education Journal, 2026)
Students' critical mathematical thinking skills are still relatively low due to the Problem-Based Learning (PBL) instructional strategy. The Realistic Mathematics Education (RME) approach, supported by students' learning discipline, is expected to enhance these abilities. This study aimed to examine the effect of the RME approach and learning discipline, both individually and interactively, on the mathematical critical thinking abilities of grade V students. The research used a quantitative experimental design with a 2x2 factorial model. A total of 60 students were selected using cluster random sampling. Instruments included a critical thinking test and a learning discipline questionnaire. Data were analysed using two-way ANOVA with a significance level of 0.05. Findings show that (1) RME significantly improved critical thinking (mean = 78.45) compared to conventional methods (mean = 70.12), F(1,56) = 6.84, p < 0.05; (2) students with high discipline scored higher (mean = 80.27) than low-discipline students (mean = 69.34), F(1,56) = 12.15, p < 0.01; and (3) there was a significant interaction between RME and discipline, F(1,56) = 4.62, p < 0.05. RME and learning discipline both positively and significantly affect students' mathematical critical thinking abilities